Development of the Double Digest Selective Label (DDSL) Typing Technique and Its Application to Staphylococcus aureus Epidemiology - V. Terletskiy; V. Tyshchenko; D.A. Myrzakozha; O.O. Zhanserkenova; Y.S. Ussenbekov; Nurbek L. Adaev (Universiti Kebangsaan Malaysia, 2014)
Bacterial typing is a key technology in human and veterinary medicine, community health, consumer protection and in agricultural research. The importance of the development of epidemiological tracking tools is underlined by numerous outbreaks of diseases due to bacterial pathogens. Particularly important is tracing pathogen dissemination in ‘real time’ i.e. to use a fast typing technique to distinguish between clonally related (epidemic) strains and unrelated (sporadic) strains. The aim of the research was to develop a fast discriminatory molecular typing technique - double digest selective label (DDSL) for Staphylococcus aureus isolates and to compare typing data with that obtained by pulsed-field gel electrophoresis. In this new typing method, large DNA fragments are produced with a restriction enzyme commonly used for PFGE but are trimmed by a second enzyme to a size which can be separated on a conventional agarose gel within a short period of time. Selective labelling of a subset of the numerous restriction fragments gives a distinct banding pattern for each isolate. Discriminatory power obtained with DDSL calculated over two different sets was higher than that of pulsed-field gel electrophoresis. Clusters of identical isolates were further resolved to unique DDSL strains. Two combinations of restriction enzymes for DDSL technique has been proposed with approximately equal discriminatory power. It has been demonstrated that DDSL approach is a fast, discriminatory alternative to other typing techniques suitable for short-term epidemiological studies.